Ympäristötuen yhteiskunnallinen kannattavuus - Vehkasalo, Ville (Maatalouden taloudellinen tutkimuslaitos, 1999)
The social costs and benefits of the Finnish Agri-Environmental Programme (FAEP) are manifold. There are several aggregate production, environmental, and farm-related effects, and the monetary valuation of these effects is not a straightforward task. However, an attempt has been made. The main objective of the FAEP is to reduce the agricultural nutrient leaching to surface and groundwaters, and the social benefits of this reduction have been approximated with the averting expenditures valuation method. That is, the value of the nutrient load reduction is the cost of a corresponding reduction in municipal wastewater treatment. The overall benefits seem to outweigh the costs of the programme. The benefit to cost ratio is roughly 2 or higher, depending on the actual reduction in nutrient leaching. The programme is beneficial even without any environmental benefits, as the 50% budget share of EU just covers the estimated farm level costs and income losses of the programme.
Social profitability of the agri-environmental programme
Keywords: Ma; ympäristötuki; vesistöjen ravinnekuormitus; kannattavuus; kustannukset; environmental benefits; monetary valuation; wastewater treatment